Cell-penetrating peptide conjugates to enhance the antitumor effect of paclitaxel on drug-resistant lung cancer - Ziqing Duan; Cuitian Chen; Jing Qin; Qi Liu; Qi Wang; Xinchun Xu; Jianxin Wang (Taylor & Francis Group, 2017)
To conquer the drug resistance of tumors and the poor solubility of paclitaxel (PTX), two PTX-cell-penetrating peptide conjugates (PTX-CPPs), PTX-TAT and PTX-LMWP, were synthesized and evaluated for the first time. Compared with free PTX, PTX-CPPs displayed significantly enhanced cellular uptake, elevated cell toxicity, increased cell apoptosis, and decreased mitochondrial membrane potential (Δψm) in both A549 and A549T cells. PTX-LMWP exhibited a stronger inhibitory effect than PTX-TAT in A549T cells. Analysis of cell-cycle distribution showed that PTX-LMWP influenced mitosis in drug-resistant A549T tumor cells via a different mechanism than PTX. PTX-CPPs were more efficient in inhibiting tumor growth in tumor-bearing mice than free PTX, which suggested their better in vivo antitumor efficacy. Hence, this study demonstrates that PTX-CPPs, particularly PTX-LMWP, have outstanding potential for inhibiting the growth of tumors and are a promising approach for treating lung cancer, especially drug-resistant lung cancer.